EVALUATION OF PERINATAL OUTCOMES IN OBSTETRIC CHOLESTASIS AND THEIR ASSOCIATION WITH MATERNAL OBSTETRIC AND BIOCHEMICAL PARAMETERS (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To assess perinatal outcomes in obstetric cholestasis and associate them with maternal obstetric and biochemical parameters. Study Design: A cross-sectional study Place and Duration: This study was carried out at Karachi Metropolitan University Abbasi Shaheed Hospital Karachi Pakistan between April 2025 to April 2026. Methods: 124 pregnant women diagnosed with obstetric cholestasis were included. Obstetric and biochemical parameters of the mother were documented, such as total bile acids, ALT, AST, GGT, and bilirubin. Perinatal outcomes measured were preterm labor, meconium-stained liquor, fetal distress, Apgar scores, admission to NICU, IUGR, respiratory distress syndrome, and stillbirth. Data were statistically analyzed using SPSS version 26, and associations were evaluated using appropriate tests (p